2015
DOI: 10.1007/s10886-015-0605-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between a Belowground Herbivore and Primary and Secondary Root Metabolites in Wild Cabbage

Abstract: Plants are attacked by both above- and belowground herbivores. Toxic secondary compounds are part of the chemical defense arsenal of plants against a range of antagonists, and are subject to genetic variation. Plants also produce primary metabolites (amino acids, nutrients, sugars) that function as essential compounds for growth and survival. Wild cabbage populations growing on the Dorset coast of the UK exhibit genetically different chemical defense profiles, even though they are located within a few kilomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…However, the effect of CRF infestation on root and leaf metabolites is debated. van Geem et al (2015) observed an increase of GSL content in one Brassica oleracea population infested by CRF and no effect on total AAs and sugars in roots. Pierre et al (2012) had the same result regarding AAs, but total root sugar content was lower in infested plants while no difference was observed on leaf metabolites.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, the effect of CRF infestation on root and leaf metabolites is debated. van Geem et al (2015) observed an increase of GSL content in one Brassica oleracea population infested by CRF and no effect on total AAs and sugars in roots. Pierre et al (2012) had the same result regarding AAs, but total root sugar content was lower in infested plants while no difference was observed on leaf metabolites.…”
Section: Discussionmentioning
confidence: 72%
“…Reported effects of AAs on insect development are also ambiguous. They could be a marker of plant nutritive quality: van Geem et al (2015) found that concentrations of histidine, asparagine, glutamine, and serine in wild cabbage were positively correlated to CRF biomass. Alternatively, they could be indirectly involved in plant defenses by providing the energy needed to produce defensive compound (Bolton, 2009) or jasmonic acid (Howe & Jander, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In B. oleracea, an increase in indole glucosinolates was recorded in roots of plants challenged by Phyllosticta brassicae caterpillars above ground, which was suggested to play a role in a negative effect on D. radicum (Soler et al, 2007). However, whether these toxins provide defence against the specialist D. radicum is debatable, because glucosinolates did not correlate with D. radicum performance in several studies (Pierre et al, 2012;Van Geem, Harvey, Cortesero, Raaijmakers, & Gols, 2015). Furthermore, D. radicum harnesses gut microbes that can disarm toxic isothiocyanates resulting from the breakdown of gluconasturtiin, an aromatic glucosinolate (Welte et al, 2015), and it may well possess methods to detoxify aliphatic and indolic glucosinolates as well.…”
Section: Discussionmentioning
confidence: 99%
“…Females lay their eggs aboveground, at the base of plant stems and, upon hatching, which occurs a few days later, larvae feed by tunneling into the roots for 2-3 weeks, before pupating in the nearby soil and emerging. Herbivory of the CRF on brassicaceous plants is known to change the concentration of primary (e.g., sugars such as glucose and sucrose) and secondary metabolites (e.g., indolyl glucosinolates) in the roots (Hopkins et al, 1999;van Dam and Raaijmakers, 2006;Pierre et al, 2012;van Geem et al, 2015). However, nothing is known about how CRF herbivory and resulting biochemical changes in the roots influence the belowground microbial communities which interact with the plant.…”
Section: Introductionmentioning
confidence: 99%